Physics with computer (Journal of Parents and Teachers, 2014)
This article presents the website called "physics with computer", in which you can find various sections (dynamics, kinematics, fluids, electromagnetism ...) with lots of information and graphics. For this reason, this web page is of great help to work with students of Bachillerato.
Keywords: web page; physics with computer; ICT; physics.